2023
DOI: 10.1044/2022_aja-22-00155
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chirp Versus Tone Burst– and Click-Evoked Masseteric Vestibular Evoked Myogenic Potentials in Normal-Hearing Adults

Abstract: Purpose: This study aimed at comparing narrowband Claus Elberling level-specific chirp (NB CE-Chirp)–, click-, and tone burst–evoked masseteric vestibular evoked myogenic potentials (mVEMPs). Method: Within-group study design and purposive sampling were performed. A total of 25 normal-hearing individuals participated in the study. The zygomatic electrode montage was used to elicit ipsilateral mVEMP responses using a 500-Hz NB CE-Chirp, a click of 100-μs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In the study, 100% of the participants had 500 Hz tone burst-evoked mVEMP and cVEMP response parameters. Similar findings have been reported previously for mVEMPs (Vignesh et al 22 ; Vinayagar et al 23 ; Neupane et al 24 )…”
Section: Discussionsupporting
confidence: 91%
“…In the study, 100% of the participants had 500 Hz tone burst-evoked mVEMP and cVEMP response parameters. Similar findings have been reported previously for mVEMPs (Vignesh et al 22 ; Vinayagar et al 23 ; Neupane et al 24 )…”
Section: Discussionsupporting
confidence: 91%
“… Neupane et al (2023) reported that the latencies of p11-n21 are shorter when elicited using clicks and 500Hz NB CE-Chirps than compared to those obtained with 500Hz tonebursts. 500Hz NB CE-Chirps tend to have earlier stimulus onset time compared to tonebursts and this could be the reason for the presence of early latencies when chirps were procured ( Çoban et al, 2021 ; Karaçaylı et al, 2020 ; Mat et al, 2021 ).…”
Section: Stimulus Parametersmentioning
confidence: 94%
“…Clicks, Chirp and tone-burst stimuli have been primarily used to record mVEMP ( Deriu et al, 2005 , 2007 ; Ginatempo et al, 2013 ; Vignesh et al, 2021 ; Romero et al, 2022 ; Sangu Srinivasan et al, 2022 ; Thirusangu and Sinha, 2022 ; Neupane et al, 2023 ; Vinayagar and Sinha, 2023 ). Vignesh et al (2021) compared the mVEMP responses obtained using tone bursts with that of those obtained with clicks in a study by de Natale et al (2015b) .…”
Section: Stimulus Parametersmentioning
confidence: 99%
See 1 more Smart Citation